Pengaruh Pendapatan Perkapita, Belanja Daerah dan Opini Audit terhadap Aksesibilitas Internet Financial Reporting pada Pemerintah Kabupaten/Kota di Sumatera Selatan - Sarumaha, Anastasia Yaniarwana; Andriani, Wiwik; Mustika, Rasyidah; Zahara, Zahara (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the influence of per capita income, regional expenditure, and audit opinions on internet financial reporting (IFR) accessibility in Regency and City Governments in South Sumatra, which consists of 17 governments. This research uses a saturated sampling method with a quantitative approach. The research results show that per capita income, regional expenditure, and audit opinion can simultaneously influence IFR accessibility in Regency and City Governments in South Sumatra. Partially, only audit opinions do not affect IFR accessibility.